Nanoparticles as transfection agents: a comprehensive study with ten different cell lines. Issue 22 (11th February 2016) - Neuhaus, Bernhard; Tosun, Benjamin; Rotan, Olga; Frede, Annika; Westendorf, Astrid M.; Epple, Matthias
Abstract : The performance of transfection agents to deliver nucleic acids into cells strongly depends on the cell type. Abstract : The performance of transfection agents to deliver nucleic acids into cells strongly depends on the cell type. In a comprehensive study, nine different cell lines and primary human mesenchymal stem cells were transfected with DNA encoding for enhanced green fluorescent protein (eGFP). As transfection agents, two kinds of cationic multi-shell calcium phosphate nanoparticles and the commercially available transfection agent Lipofectamine were used. The transfection efficiency was measured by fluorescence microscopy by counting the percentage of green fluorescent cells which expressed eGFP as well as qPCR. Furthermore, the uptake of fluorescent calcium phosphate nanoparticles was measured by fluorescence microscopy. The cell viability was measured by the MTT test after incubation with nanoparticles and Lipofectamine. All cell types took up nanoparticles (with different efficiency), but the expression of eGFP was strongly different, demonstrating that the uptake not necessarily leads to processing of a gene. A clear correlation was found between the transfection efficiency and the cell viability that was independent on the transfection agent: a high transfection efficiency was clearly correlated with a low cell viability and vice versa .